Studi Kelayakan Pendirian Perusahaan OPP di Kota Sidoarjo - Rachmadi, ellysa Lucia; bendatu, liem yenny (Jurnal Titra, 2015)
This research aimed to determine the feasibility of OPP plastic Company establishment at Sidoarjo. The research consists of market aspect, technical aspect, legal aspect, and financial aspect. Data collection for market analysis is obtained from three plastic stores at Surabaya and interview method is used to get to know the competitor condition. The forecasting result in technical analysis is used as the input to find out the number of the folding and sealing machine. The number of machine is used to calculate how many operator the company should hire. After that, legal analysis is to know the legality of company establishment. The company requires initial investment Rp.670,693,900.00 and will reach break even point after 49 months with the 5 years internal rate of return 16.1%. Hence, this study is feasible by considering the market aspect, technical aspect, legal aspect, and financial aspect.